CSF YKL‐40 and GAP‐43 are related to suicidal ideation in older women. (17th February 2017) - Rymo, I.; Kern, S.; Bjerke, M.; Zetterberg, H.; Marlow, T.; Blennow, K.; Gudmundsson, P.; Skoog, I.; Waern, M.
Abstract : Objective: To investigate possible relationships between suicidal ideation and cerebrospinal fluid (CSF) levels of glial markers YKL‐40 (also known as chitinase‐3‐like protein 1), growth‐associated protein‐43 (GAP‐43) and myelin basic protein (MBP). Method: The sample was obtained from the Prospective Population Study of Women and included 86 women without dementia who underwent both psychiatric examinations and lumbar puncture (LP). Eight of these women reported past‐month suicidal ideation. Results: Significantly, higher CSF levels of both YKL‐40 and GAP‐43 were detected in women with past‐month suicidal ideation. Associations with suicidal ideation remained for both YKL‐40 and GAP‐43 in regression models adjusted for smoking status, BMI and age. CSF levels of YKL‐40, GAP‐43 and MBP did not differ by depression status. Higher levels of CSF GAP‐43 were associated with feelings of worthlessness; a strong relationship was demonstrated in the fully adjusted model (OR 5.95 CI [1.52–23.20], P = 0.01). Conclusion: Our findings of elevated CSF concentrations of both YKL‐40 and GAP‐43 in women with suicidal ideation, compared to those without, suggest that a disrupted synaptic glial functioning and inflammation may be related to the aetiology of suicidal ideation in older adults.